Overexpression of GSK-3β in Adult Tet-OFF GSK-3β Transgenic Mice, and Not During Embryonic or Postnatal Development, Induces Tau Phosphorylation, Neurodegeneration and Learning Deficits - Rodríguez-Matellán, Alberto; Avila, Jesús; Hernández, Félix (Frontiers in Molecular Neuroscience, 2020)
GSK-3β or tau-kinase I is particularly abundant in the Central Nervous System, playing a key role in the pathogenesis of Alzheimer´s disease. Accordingly, transgenic mouse models overexpressing this kinase recapitulate some aspects of this disease, such as tau hyperphosphorylation, neuronal death, and microgliosis. These alterations have been studied in mouse models showing GSK-3β overexpression from birth. In this case, some of these alterations may be due to adaptations that occur during development. Here we explored the potential of the Tet-OFF conditional system in the murine CamKIIα-tTA/GSK-3β model to increase the activity of GSK-3β only during adulthood. To this end, the overexpression of GSK-3β remained OFF during embryonic and postnatal development by administration of doxycycline in drinking water for six months, while it was turned ON in adult animals by removal of the treatment for six months. In these conditions, the CamKIIα-tTA/GSK-3β mouse is characterized by an increase in phosphorylated tau, cell death, and microgliosis. Furthermore, the increase in GSK-3β expression in the adult animals triggered a cognitive deficit, as determined through the hippocampus-dependent object recognition test. These results demonstrate that the GSK-3β plays a key role in Alzheimer´s disease and that previously published data with other transgenic models are neither caused by or a consequence of adaptations to high levels of the enzyme during development.